Pengaruh Audit Firm Rotation, Komite Audit, dan Audit Capacity Stress Terhadap Kualitas Audit: Studi Empiris pada Perusahaan Sub Sektor Bank yang Terdaftar di BEI Periode 2018-2022 - Raka Aththaariq Akhbar; Nurzi Sebrina (Universitas Negeri Padang, 2024)
This research aims to empirically prove the influence of audit firm rotation, audit committee and audit capacity stress on audit quality in banking sub-sector companies on the Indonesian Stock Exchange. In this research, 30 banking companies were used. The sampling technique used was purposive sampling. The data analysis method used in hypothesis testing is binary logistic regression and Wald test. In accordance with the results of hypothesis testing processed using the SPSS program, it was found that audit firm rotation had no significant effect on audit quality in banking sub-sector companies on the Indonesia Stock Exchange. In the second hypothesis testing stage, it was found that the audit committee had a positive and significant effect on audit quality in banking sub-sector companies on the Indonesia Stock Exchange, while in the third hypothesis testing results it was successfully proven that audit capacity stress had a negative and significant effect on audit quality in sub-sector companies. Banking on the Indonesian Stock Exchange. In accordance with the results of hypothesis testing obtained, it is recommended that companies continue to optimize the role of the audit committee as part of the monitoring instruments within the company. When the role of the audit committee runs well and consistently, the quality of the audit will be better. Through strict supervision, the possibility of fraud will be smaller so that the quality of the resulting audit will be higher and beneficial for stakeholders, especially investors.